Fluorophore-doped core–multishell spherical plasmonic nanocavities : resonant energy transfer toward a loss compensation - Peng, Bo (2013)
Plasmonics exhibits the potential to break the diffraction limit and bridge the gap between electronics and photonics by routing and manipulating light at the nanoscale. However, the inherent and strong energy dissipation present in metals, especially in the near-infrared and visible wavelength ranges, significantly hampers the applications in nanophotonics. Therefore, it is a major challenge to mitigate the losses. One way to compensate the losses is to incorporate gain media into plasmonics. Here, we experimentally show that the incorporation of gain material into a local surface plasmonic system (Au/silica/silica dye core–multishell nanoparticles) leads to a resonant energy transfer from the gain media to the plasmon. The optimized conditions for the largest loss compensation are reported. Both the coupling distance and the spectral overlap are the key factors to determine the resulting energy transfer. The interplay of these factors leads to a non-monotonous photoluminescence dependence as a function of the silica spacer shell thickness. Nonradiative transfer rate is increased by more than 3 orders of magnitude at the resonant condition, which is key evidence of the strongest coupling occurring between the plasmon and the gain material.